A Case study of “Necklacing”: When the case has a face - Laubscher, Leswin; Mbuqe, Sipho (PINS-Psychology in Society, 2022)
This article reports on, and develops, existing studies by Mbuqe (2010), and Mbuqe & Laubscher (2019). Political violence is the general phenomenon of interest, research and theoretical access to which is granted by a close examination of the “necklacing” murder of Ms. Nombulelo Julia Nokwakwha Dilato in Colesberg, South Africa, on the 2nd of October, 1985. The authors illustrate how their research was upset and troubled by a particular incident – the perpetrators throwing sand on the face of the victim in order for it not to burn – and how revisiting that incident dramatically changed the course and understanding of their research. The authors conclude by suggesting an ethical scholarship, influenced by the work of the philosopher Emmanuel Levinas, as well as the imperatives of Unobuntu.